Deterring neighborhood gangs in accordance with Law 20-03 of August 30, 2020 related to the prevention and control of neighborhood gangs -An analytical study- - عقباوي محمد عبد القادر (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2022)
The objective of this topic is; Studying the efficacy of the penalties, methods and mechanisms addressed by the legislator through Law No. 20/03 in combating neighborhood gangs at the local and national levels, by analyzing the texts contained in this law; In terms of concepts and mechanisms of prevention and deterrence. The Algerian legislator has graded in terms of tightening the penalties imposed on the perpetrators of neighborhood gang crimes according to the seriousness of each of the acts constituting these crimes, as they begin in the form of simple acts punishable by imprisonment and then progress to crimes that reach the penalty of life imprisonment.